1992
DOI: 10.1111/j.1600-0528.1992.tb00679.x
|View full text |Cite
|
Sign up to set email alerts
|

The University of North Carolina Caries Risk Assessment study: further developments in caries risk prediction*

Abstract: Over 4000 first and fifth grade children from the areas surrounding Aiken, South Carolina, and Portland, Maine, participated in a 4-yr study to develop caries risk assessment models. The predictors used at baseline included detailed clinical examinations, salivary microbiological tests, and sociodemographic and dental behavior data. Mean 3-yr caries increments in South Carolina were twice those in Maine. For the four risk assessment models (two grade cohorts at two sites) specificity values averaged 0.83 and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
136
1
11

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(161 citation statements)
references
References 27 publications
13
136
1
11
Order By: Relevance
“…A recent study in Singapore showed that caries prediction based on a questionnaire reached a sensitivity/specificity of 0.82/0.81 in 3-to 6-year-olds (Gao et al, 2010). However, additional risk factors (e.g., plaque, bacterial tests, salivary factors, exposure to fluoride) do not seem to markedly improve the prediction in older schoolchildren, adolescents, and adults (Disney et al, 1992;Vanobbergen et al, 2001; Stenlund et al, 2002;Twetman and Fontana, 2009). This may be explained in part by the fact that caries experience reflects relatively well both past and current interplay between and among the various etiologic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in Singapore showed that caries prediction based on a questionnaire reached a sensitivity/specificity of 0.82/0.81 in 3-to 6-year-olds (Gao et al, 2010). However, additional risk factors (e.g., plaque, bacterial tests, salivary factors, exposure to fluoride) do not seem to markedly improve the prediction in older schoolchildren, adolescents, and adults (Disney et al, 1992;Vanobbergen et al, 2001; Stenlund et al, 2002;Twetman and Fontana, 2009). This may be explained in part by the fact that caries experience reflects relatively well both past and current interplay between and among the various etiologic factors.…”
Section: Discussionmentioning
confidence: 99%
“…For a clinician, the concepts of risk assessment and prognosis are an essential part of clinical decision-making. In fact, the dentist's overall subjective impression of the patient might have good caries-predictive power (Disney et al, 1992), but it is unclear how this information is incorporated into everyday practice. A recent survey of US practices suggests that a significant proportion of dentists had yet to adopt treatments based on assessment of caries risk (Riley et al, 2010), even when multiple expert-opinion tools are available for children [e.g., Caries Assessment Tool-CAT of the American Academy of Pediatric Dentistry, developed for use in multiple settings (2007); the American Dental Association's Caries Risk Tool (2008); the Caries Management by Risk Assessment tool (Ramos-Gomez et al, 2007)].…”
Section: Introductionmentioning
confidence: 99%
“…107 Since CRA identifies an individual's potential for developing caries at a given time, the assessment should be made regularly throughout life and risk management instituted accordingly. 104,108,109 As a multifactorial disease, no single risk factor or combination of factors has been identified to predict future caries with both high positive predictive values and high negative predictive values. In addition to the presence of cariogenic bacteria in the dental biofilm, environmental risk factors such as diet, past caries experience, saliva, medical conditions and suboptimal fluoride exposure are implicated.…”
Section: Sweet Drinks and General Health Of Childrenmentioning
confidence: 99%
“…In addition to the presence of cariogenic bacteria in the dental biofilm, environmental risk factors such as diet, past caries experience, saliva, medical conditions and suboptimal fluoride exposure are implicated. 32,105,106,[108][109][110][111][112][113] Control of these risk factors can alter the ecology of the biofilm and the subsequent likelihood of caries. Dietary risk factors include the amount of sugars consumed, manner of consumption, frequency of exposure and retentiveness.…”
Section: Sweet Drinks and General Health Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation